RESULTS OF TYPE-III SUPRACONDYLAR FRACTURE HUMERUS WITH OPEN REDUCTION AND INTERNAL FIXATION IN CHILDREN AFTER FAILED CLOSED REDUCTION - Khan, Mohammad Ayaz; Khan, Alamzeb; Hakeem, Awal; Askar, Zahid; Durrani, Naeem; Durrani, Mohammad Zaffar; Idrees, Mohammad; Ahmad, Israr (Journal of Ayub Medical College Abbottabad, 2010)
Background: Supracondylar fracture of humerus is the second most common fracture in children which account for 60-75% of all fractures around the elbow. There are various treatment modalities for type-III fracture, i.e., closed reduction and casting, skeletal traction, close reduction and percutaneous pinning and open reduction and internal fixation. This study was conducted to see the outcome of open reduction and internal fixation after failed closed reduction. Methods: This study was conducted in the Orthopaedics Departments of Khyber Teaching Hospital Peshawar and Ayub Teaching Hospital Abbottabad from February 2007 to Nov 2007 on 30 children. Patients included were of either gender with age range from 5-12 years with displaced supracondylar fracture (typeIII) after failed closed reduction. All fractures were fixed with two cross K-wires by open reduction and internal fixation. The patients were assessed both clinically and radiologically and results were tabulated according to Flynn criteria. Results: Twenty-eight patients had excellent results while two had good results according to Flynn criteria. None of the patients had either fair or poor result. Conclusion: Open reduction and internal fixation is a good and reliable method after failed closed reduction and gives stable fixation with anatomical alignment. Keywords: Type-III Supracondylar fracture, open reduction and internal fixation